2017
DOI: 10.1002/bmc.4114
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic analysis of the antidepressive effects of Yangxinshi Tablet in a vascular depression model in mice

Abstract: In recent years, vascular depression has become the focus of international attention. Yangxinshi Tablet (YXST) is usually used in cthe linic for the treatment of arrhythmia and heart failure, but we found that it also has antidepressive effects. The objective of the study was to identify biomarkers related to vascular depression in hippocampus and explore the antidepressive effects of YXST on the mouse model. Untargeted metabolomics based on UHPLC-Q-TOF/MS was applied to identify significantly differential bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…54 Histamine is also a neurotransmitter, and disruption of histamine neurotransmission affects behavioral response. 55 In this study, histamine showed the largest fold change (0.7801) among metabolites with a significant t-test ( p = 0.001) between control and stress-like zebrafish brain model. Kano et al reported a significant decrease in histamine H 1 receptor binding in depressed patients and suggested an important role of histaminergic neuro system in pathophysiology of depression.…”
Section: Discussionmentioning
confidence: 54%
“…54 Histamine is also a neurotransmitter, and disruption of histamine neurotransmission affects behavioral response. 55 In this study, histamine showed the largest fold change (0.7801) among metabolites with a significant t-test ( p = 0.001) between control and stress-like zebrafish brain model. Kano et al reported a significant decrease in histamine H 1 receptor binding in depressed patients and suggested an important role of histaminergic neuro system in pathophysiology of depression.…”
Section: Discussionmentioning
confidence: 54%
“…Suggesting pharmacological pleiotropy, Yangxinshi tablets have been shown to be effective in treating depression/anxiety through both direct mechanisms and indirectly as a consequence of angina relief. [19] In the HEARTRIP trial, we will use the PHQ-9 depression scale and the GAD-7 anxiety screening scale to assess the effects of Yangxinshi tablets on depression and anxiety. The Seattle Angina Questionnaire, a well-established tool to measure patients’ health status, will also be used to evaluate frequency and intensity of angina and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…CR as a multidisciplinary and promising program can also effectively relieve depression and anxiety, thus improve QoL in patients with CHD. [ 34 36 ] Previous studies reported the effects of YXS on improving depression-like behaviors, [ 15 ] its role in CR still needs further investigation. The safety of the YXS tablet will be evaluated as patients’ symptoms and laboratory tests, such as blood routine, urine routine, liver and renal function, and echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely used for the treatment of CHD, relieving symptoms of angina pectoris, and protecting myocardial ischemia. [ 15 ] A previous study has already reported the effects of promoting rehabilitation after the percutaneous coronary intervention with no obvious side effect, [ 16 ] whether it could help improve EC for patients with CHD is still unclear. Our study aims to investigate the efficacy and safety of YXS tablet on the exercise tolerance in CHD and its role in the CR program.…”
Section: Introductionmentioning
confidence: 99%